Multifunctions of Pleurotus sajor-caju (Fr.) Singer: a highly nutritious food and a source for bioactive compounds - Finimundy, Tiane C. (2018)
A study with Pleurotus sajor-caju was conducted to: evaluate the nutritional and chemical composition of the fruiting bodies; optimize the preparation of bioactive phenolic extracts; and characterize the optimized extract in terms of bioactive compounds and properties. P. sajor-caju revealed an equilibrated nutritional composition with the presence of hydrophilic (sugars and organic acids) and lipophilic (tocopherols and PUFA) compounds. p-Hydroxybenzoic, p-coumaric and cinnamic acids were identified in the extract obtained with ethanol (30 g/l ratio) at 55 °C for 85 min. This extract showed antioxidant properties (mainly reducing power and lipid peroxidation inhibition), antibacterial activity against MRSA and MSSA and cytotoxicity against NCI-H460, MCF-7 and HeLa. Furthermore, as the extract showed capacity to inhibit NO production in Raw 264.7 macrophages, molecular docking studies were performed to provide insights into the anti-inflammatory mechanism of action, through COX-2 inhibition by the phenolic acids identified.